Peningkatan Kapasitas Legislasi Apartur Desa melalui Pendampingan Penyusunan Peraturan Desa di Desa Tanjung, Pademawu, Pamekasan - Ansori, Ansori; Dewi Muti’ah; Aprilina Pawestri (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The capacity of village officials to understand village legislative procedures is a key factor in realizing accountable and law-based village governance. However, conditions in Tanjung Village, Pademawu District, Pamekasan Regency indicate that village officials' understanding of the village regulation drafting process is still limited, and there are no regulations regarding the management of village tourism potential. This community service activity aims to improve the legislative capacity of village officials through technical assistance in drafting Village Regulations (Perdes). The method used was a participatory approach through field observations, Focus Group Discussions (FGDs), village legal education, and assistance in drafting simple academic papers and Perdes drafts. The activity results indicate an increased understanding of legislative mechanisms among village officials and the development of a draft Village Regulation on Village Tourism Management, which has been submitted to the Tanjung Village Government as one of the main outputs. Furthermore, this activity contributed to the formation of a local legal culture and increased village government participation in the legislative process. This mentoring model can be replicated in other villages as a strategy to strengthen village governance based on regulations and local needs